Markaların Sosyal Medya Kullanımının Tüketici Davranışı Üzerindeki Etkileri - Aytan, Cansu; Telci, Emine Eser (The Turkish Online Journal of Design Art and Communication, 2014)
With the development of the technology, Internet usage became a habit in everyday life which made the social media indispensable. Social media lets users to get in touch with other users via interactive communication. Users that share every moment and experience of their daily life, are being effective on other consumers’ behaviors and manners towards the created brand image with the content that they share. As a result, brands are shaping their brand images and consumers’ attitudes towards themselves, by using social media marketing and taking care of consumer requests. At this point, consumers may purchase products, being affected with the contents and attitude towards the brand image formed by the social media users and brands’ themselves. In this study; brands' social media usage and its effects on consumer attitudes and behavior have been investigated. At the theoretical section of the study; a thorough literature review is conducted on social media, social media marketing, brand image, brand attitude, and consumer behavior. Then, during the research process, a survey on the effects of brands' social media usage on consumers is prepared and has been responded by 465 social media users. With the analysis of the given answers, it has been established that the brands’ uses of social media have been identified to influence consumers' behavior.
Keywords: Sosyal Medya; Sosyal Medya Pazarlama; Marka İmajı; Marka Tutumu; Tüketici Davranışı; Social Media; Social Media Marketing; Brand Image; Brand Attitude